Distribution and functions of TonB-dependent transporters in marine bacteria and environments: implications for dissolved organic matter utilization. - Kai Tang (Public Library of Science (PLoS), 2012)
Background Bacteria play critical roles in marine nutrient cycles by incorporating and redistributing dissolved organic matter (DOM) and inorganic nutrients in the ocean. TonB-dependent transporter (TBDT) proteins allow Gram-negative bacteria to take up scarce resources from nutrient-limiting environments as well as siderophores, heme, vitamin B12, and recently identified carbohydrates. Thus, the characterization of TBDT distribution and functions is essential to better understand the contribution TBDT to DOM assimilation and its consequences on nutrient cycling in the environment. Methodology/principal findings This study presents the distribution of encoded known and putative TBDT proteins in the genomes of microorganisms and from the Global Ocean Survey data. Using a Lek clustering algorithm and substrate specificities, the TBDT sequences were mainly classified into the following three groups: (1) DOM transporters; (2) Siderophores/Vitamins transporters; and (3) Heme/Hemophores/Iron(heme)-binding protein transporters. Diverse TBDTs were found in the genomes of oligotroph Citromicrobium bathyomarinum JL354 and Citromicrobium sp JLT1363 and were highly expressed in the stationary phase of bacterial growth. The results show that the Gammaproteobacteria and the Cytophaga-Flavobacterium-Bacteroides (CFB) group bacteria accounted for the majority of the TBDT gene pool in marine surface waters. Conclusions/significance The results of this study confirm the ecological importance of TBDTs in DOM assimilation for bacteria in marine environments owing to a wide range of substrate utilization potential in the ubiquitous Gammaproteobacteria and CFB group bacteria.